2010
DOI: 10.19030/jber.v8i11.50
|View full text |Cite
|
Sign up to set email alerts
|

The Lasting Effects Of Social Media Trends On Advertising

Abstract: <p style="text-align: justify; margin: 0in 0.5in 0pt; mso-pagination: none;"><em style="mso-bidi-font-style: normal;"><span style="font-size: 10pt;"><span style="font-family: Times New Roman;">Americans are exposed to an astounding number of advertising messages every day.<span style="mso-spacerun: yes;">&nbsp; </span>The result of this bombardment of advertising on society is that consumers have become increasingly resistant to traditional forms of advertising.<span … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Regarding the users' engagement behaviour in social media, advertising, sharing, commenting, and creating all strengthened the relationships among the social community members. Therefore, we infer that marketers should employ social marketing to strengthen the relationships among social community members, products, and brands to create relationship attachment, as suggested by Shevlin (2007), Khanfar et al (2010), andLuarn et al (2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the users' engagement behaviour in social media, advertising, sharing, commenting, and creating all strengthened the relationships among the social community members. Therefore, we infer that marketers should employ social marketing to strengthen the relationships among social community members, products, and brands to create relationship attachment, as suggested by Shevlin (2007), Khanfar et al (2010), andLuarn et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Goyal (2013) described how social media advertising, which involves placing advertising messages on social media websites, yields maximum profits by accessing user information and then displaying specific advertising messages for target audiences. Khanfar et al (2010) found that advertisers who apply customer marketing through social media advertising create more favourable relationships between brands and customers.…”
Section: Theoretical Background Social Media Advertisingmentioning
confidence: 99%
“…Para lograr viralidad, el mensaje debe ser memorable e invitar a la acción, pero para eso, tanto el mensajero como el mensaje son importantes (18). Crear contenidos con valor real es esencial para lograr interacción efectiva con las personas, lo cual va más allá de un simple retroalimentación (19). Es en este punto, donde más deben trabajar los departamentos de salud pública que utilizan la web, ya que más allá de acumular contenidos, se trata de capitalizar la interacción con el público y si el mensajero ha perdido prestigio, lo prioritario es reconstruir la reputación y la confianza, y allí, la innovación es vital.…”
Section: Discussionunclassified
“…Shock Advertising is a "powerful advertising tactic to capture the target audience's attention and encourage advertising processing, as it deliberately violates social norms" (Dahl, Frankenberger & Manchanda 2003). Grabbing consumer attention is very challenging and essential for marketers, as consumers are bombarded by thousands of adverts daily (Wright et al 2016). Recently, "the advertising environment is highly competitive, this intense competition drove marketers to search for more effectual strategies grabbing the audience attention.…”
Section: Social Marketing and Shock Advertisingmentioning
confidence: 99%